Quality assurance in additive manufacturing of thermoplastic parts: predicting consolidation degree based on thermal profile. (27th June 2019) - Roy, Mriganka; Wodo, Olga
Additive manufacturing is one of the most prominent and promising technologies in the field of manufacturing. However, its current dissemination is largely limited to the prototyping role due to inadequate quality assurance. The detailed process-geometry-property relationships are still to be unveiled, despite AM being a highly repetitive process. In this work, we aim to address this gap of insight by leveraging a numerical approach in predicting the thermal behaviour of the deposition to quantify the properties of the printed part. In particular, we present a prediction of the consolidation strength in fused filament fabrication. The proposed protocol is universal and can be applied to any deposition condition and geometry. This contribution has important implication for prefabrication quality assurance in AM as it allows to link process parameters with part properties for any geometry hence opening new avenues for process optimisation.